Penguatan Ekstrakurikuler berbasis Pendampingan untuk Meningkatkan Keterampilan Berbahasa Inggris Siswa SMP - Batubara, Riska; Ardiyansah, Tri Yuli; Salsabila, Aliyah; Khudzaifah, Yolanda Nafisya (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
English language proficiency is an essential competency that students must possess to face global competition. However, various challenges are still encountered by educational institutions, particularly at the junior high school (SMP) level, including limited teaching resources, low student motivation, and suboptimal utilization of extracurricular programs. SMP Islam Manbaul Ulum Gresik faces similar challenges, where students' English proficiency remains relatively low. In response to this issue, this community service program was carried out with the aim of supporting the improvement of students’ English skills through the strengthening of an extracurricular program based on mentoring and training. The program was designed through four systematic stages: needs mapping, activity planning, implementation, and evaluation. The main strategies included training for mentor teachers, developing interactive materials, and conducting workshops for students. The results of the activity showed significant improvement in students’ language skills, active participation, and students’ confidence. These findings indicate that the development of contextual and collaborative extracurricular programs can serve as an effective approach to enhance English proficiency among junior high school students.